GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 292 species occurrences available in GBIF matching the query: TaxonKey: 4372749. The dataset includes 292 records from 37 constituent datasets: 1 records from CAS Invertebrate Zoology (IZ). 1 records from IndOBIS, Indian Ocean Node of OBIS. 17 records from MAL. 2 records from University of California Museum of Paleontology. 25 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Natal Museum - Mollusc Collection (AfrOBIS). 3 records from Paleobiology Database. 1 records from DBL_Life. 2 records from KU Museum of Invertebrate Paleontology. 1 records from Invertebrate specimens in the Wakayama Prefectural Museum of Natural History, Japan.. 1 records from Academy of Natural Sciences OBIS Mollusc Database. 4 records from Natural History Museum (London) Collection Specimens. 3 records from Lund Museum of Zoology (MZLU). 3 records from Recent Invertebrates Specimens. 34 records from invertebratezoology. 10 records from Shellfish specimens in the NISHINOMIYA SHELL MUSEUM, Japan.. 11 records from SysTax - Zoological Collections. 2 records from NPL collections. 1 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from International Fossil Shell Museum (NL) - Mollusca Collection. 43 records from Naturalis Biodiversity Center (NL) - Mollusca. 2 records from Biologiezentrum Linz. 4 records from Marine invertabrate(Mollusca) specimen database of Osaka Museum of Natural History. 2 records from Bernice P. Bishop Museum. 5 records from Northern Territory Museum and Art Gallery provider for OZCAM. 2 records from Invertebrate Paleontology Division, Yale Peabody Museum. 1 records from Mollusca specimens of Toyama Science Museum. 3 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 1 records from NMNH occurrence DwC-A. 15 records from Australian Museum provider for OZCAM. 2 records from Queensland Museum provider for OZCAM. 1 records from Invertebrate Zoology Division, Yale Peabody Museum. 25 records from Naturalis National Natural History Museum (NL) – Indo-Pacific Plio-Pleistocene fossils. 1 records from RBINS collections. 38 records from Museum of Comparative Zoology, Harvard University. 2 records from Molluscan specimen database of Kanagawa Prefectural Museum of Natural History. 21 records from Natural History Museum Rotterdam (NL) - Mollusca collection.
Keywords: GBIF; biodiversity; species occurrences